Paradigm shift in management of acute iatrogenic colonic perforations: 24-year retrospective comprehensive study - Paspatis, Gregorios A.; Fragaki, Maria; Velegraki, Magdalini; Mpitouli, Afroditi; Nikolaou, Pinelopi; Tribonias, Georgios; Voudoukis, Evangelos; Karmiris, Konstantinos; Theodoropoulou, Angeliki; Vardas, Emmanouil (Endoscopy International Open, 2021)
Background and study aims Through advanced endoscopic clipping techniques, endoscopic treatment of both diagnostic and therapeutic acute iatrogenic colonic perforations has been shown effective. The main purpose of this study was to compare the management of acute iatrogenic perforations (AIPs) of the colon before and after the introduction of advanced clipping techniques.Methods We conducted a retrospective study from July 1996 to February 2020. The period was divided into two sub periods, Period 1: from July 1996 to December 2012 and Period 2: from January 2013 to March 2020. All AIPs occurring during a colonoscopy and detected during or immediately (< 4 hours) after the procedure, were included in the study. Results The total number of colonoscopies performed at our hospital was 33055 and 36831 during Periods 1 and 2 respectively. Fifteen perforations were observed in Period 1 and 11 in Period 2. The rate of surgery was 93.3 % % (14/15) in Period 1 and 27.2 % (3 /11) in Period 2 (P < 0.01). The mean hospital stay in Period 1 was 6.9 days and 4 in Period 2 (P < 0.01). Conclusions Data from this historical cohort have clearly shown a decrease in the surgery rate and the length of hospitalization of AIPs in Period 2 compared to Period 1.